Electrochemical studies of p-sulfonatocalix[4]arene in ionic liquid as supporting electrolyte - Abdul Manan, Ninie Suhana; Hardacre, Chris; Basirun, Wan Jeffrey; Alias, Yatimah (Malaysian Journal of Science, 2010)
The electrochemical behaviour of sodium p-sulfonatocalix[4]arene (s-psc4) was studied. In this study ionic liquid/water mixtures were used as electrolyte, namely, [BMIM][BF4]/water mixture and [BMIM][OTf]/water mixture ([BMIM] = 1-butyl 3-methyl imidazolium, BF4 = tetrafluoroborate, OTf = trifluoromethanesulfonate). S-psc4 can be oxidised at 0.84 V and 0.83 V in [BMIM][BF4]/water and [BMIM][OTf]/water respectively. The reaction is an irreversible process for both systems. The number of electron transferred in this electrochemical process is one electron and the diffusion coefficient, (D) for both systems was 1.15 x 10-8 cm2 s-1 and 1.67 x 10-8 cm2 s-1 respectively. The anodic potentials were affected by temperature and the activation energy, (Ed) was 18.18 kJ mol-1 and 18.78 kJ mol-1 in [BMIM][BF4]/water mixture and [BMIM][OTf]/water mixture respectively.